2016
DOI: 10.3390/ijms17111925
|View full text |Cite
|
Sign up to set email alerts
|

3D Visualization of Developmental Toxicity of 2,4,6-Trinitrotoluene in Zebrafish Embryogenesis Using Light-Sheet Microscopy

Abstract: Environmental contamination by trinitrotoluene is of global concern due to its widespread use in military ordnance and commercial explosives. Despite known long-term persistence in groundwater and soil, the toxicological profile of trinitrotoluene and other explosive wastes have not been systematically measured using in vivo biological assays. Zebrafish embryos are ideal model vertebrates for high-throughput toxicity screening and live in vivo imaging due to their small size and transparency during embryogenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…This result is in conjunction with body length shortening by dimethachlor. Also, elevated apoptosis might result in defects in the vascular and neural systems in the posterior regions, which negatively affects whole embryogenesis (Eum et al, 2016;Chen et al, 2017). Dimethachlor generated not only apoptotic cells but also ROS, which adversely affected embryonic organogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…This result is in conjunction with body length shortening by dimethachlor. Also, elevated apoptosis might result in defects in the vascular and neural systems in the posterior regions, which negatively affects whole embryogenesis (Eum et al, 2016;Chen et al, 2017). Dimethachlor generated not only apoptotic cells but also ROS, which adversely affected embryonic organogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…TNT and its associated explosive compounds cause pollution if this water is delivered to the soil without purification [5]. TNT contamination from TNT-containing pink water in military regions has also been reported by researchers in the literature [5,7]. Chusova et al [5] collected TNT contaminated pink water released from a treatment plant at the demilitarisation factory Nammo Vingakersverken AB and they stated that the TNT level in the pink water was 12mM after serial dilutions (5 times) and removing of the insoluble components.…”
Section: Introductionmentioning
confidence: 89%
“…Chusova et al [5] collected TNT contaminated pink water released from a treatment plant at the demilitarisation factory Nammo Vingakersverken AB and they stated that the TNT level in the pink water was 12mM after serial dilutions (5 times) and removing of the insoluble components. Eum et al [7] collected pink water from Agency for Defense Development, Daejeon, Korea for researching the effects of TNT-contaminated pink water in Zebrafish embryogenesis. They stated that the amount of TNT in the pink water was 45.54 mg/L.…”
Section: Introductionmentioning
confidence: 99%
“…Nitrocellulose industry wastewater is highly toxic to the environment because it contains chlorophenols, chlorolignins, organic acids, acid resins, and dioxins [23,32], as well as high levels of organic matter and metal ions [22]. There are few studies analyzing the toxicity of nitrocellulose to aquatic organisms [37-39], but many studies reported the detrimental effects of other explosives, such as 2,4,6-trinitrotoluene (TNT), 1,3,5-Trinitroperhydro-1,3,5-triazine (RDX), and 1,3,5,7tetranitro-1,3,5,7-tetrazocane (HMX) [40][41][42][43][44][45][46].…”
Section: Cbmentioning
confidence: 99%